LTCM Redux? Hedge fund Treasury trading, funding fragility, and risk constraints - Kruttli, Mathias S.; Monin, Phillip J.; Petrasek, Lubomir; Watugala, Sumudu W. (Journal of Financial Economics, 2025)
We exploit the 2020 Treasury market shock to analyze how external and internal constraints impact arbitrageurs. Using regulatory filings, we find that hedge funds reduced arbitrage activities and increased cash holdings, despite stable credit and low contemporaneous redemptions. Creditors’ regulatory and liquidity constraints were not propagated to hedge funds through repo—Treasury arbitrageurs’ predominant financing source. Fund-creditor borrowing data reveal more regulated dealers provided, and more important clients received, disproportionately higher funding. Value-at-risk reported by funds suggests internal risk constraints were binding. Our results support theoretical predictions that arbitrageur risk constraints and precautionary liquidity management can amplify market instability even when contemporaneous financing remains resilient.